HUBUNGAN ANTARA KETAHANAN KARDIOVASKULAR DANAKTIVITAS FISIK DENGAN TEKANAN DARAH PADA MAHASISWAUSIA 18-21 TAHUN DI FAKULTAS KEDOKTERAN UPNVJ - Regita Siska Ananda Yusup (2023)
Introduction: High blood pressure or hypertension is an increase of systolic blood pressure exceeding 140 mmHg and diastolic blood pressure exceeding 90 mmHg in measurements made 2 times with an interval of five minutes in a state of sufficient rest or calm. The prevalence of hypertension in Indonesia based on the 2018 Riskesdas in residents aged > 18 years has a prevalence of 34.11%. Blood pressure can be affected by several factors, both uncontrollable and controllable, one example of a controllable factor is cardiovascular endurance and physical activity. Aims: To determine the relationship between cardiovascular endurance and physical activity with blood pressure in students aged 18-21 years at the Faculty of Medicine UPNVJ. Method: This study is an analytic observational study using a cross-sectional approach. The study was conducted from October 2022 to November 2022. The number of samples used was 78 people who met the inclusion and exclusion criteria. Retrieval of data using the probability method by means of simple random sampling. Statistical data analysis used Fisher's alternative test. Results: The results of the analysis using the alternative Fisher endurance test obtained a relationship between cardiovascular and blood pressure (p = 0.038) and between physical activity and blood pressure (p = 0.038). Conclusion: There are many benefits of training cardiovascular endurance and doing physical activity for the future, one of which is to reduce the risk of an increase in blood pressure. Starting cardiovascular endurance training and physical activity can be done from simple things like jogging, swimming, cycling, walking, and so on